2003
DOI: 10.1016/s0378-1097(03)00479-8
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of 14-3-3 proteins inToxoplasma gondiitachyzoites and evidence for a lipid raft-associated form

Abstract: A polyclonal antibody was raised against a Toxoplasma gondii 14-3-3^gluthatione S-transferase fusion protein obtained by cloning a 14-3-3 cDNA sequence determined from the T. gondii database. This antibody specifically recognized T. gondii 14-3-3 without any crossreaction with mammalian proteins. Immunofluorescence microscopy studies of the tachyzoites or the T. gondii-infected cells suggested cytosolic and membranous localizations of 14-3-3 protein. Different subcellular fractions were prepared for electropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…The localization of 14-3-3 proteins in different subcellular compartments and in association with membrane proteins has been widely demonstrated (37,38), and a lipid raft-associated form of the T. gondii 14-3-3 homolog has been recently described (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The localization of 14-3-3 proteins in different subcellular compartments and in association with membrane proteins has been widely demonstrated (37,38), and a lipid raft-associated form of the T. gondii 14-3-3 homolog has been recently described (13).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies, which have mainly focused on expression and localization, have been conducted on Plasmodium falciparum, Plasmodium knowlesi, Toxoplasma gondii, and Eimeria tenella, and the results have suggested that 14-3-3s play a role in the transmission of the regulatory signals involved in a wide array of biological processes, including the proliferation and migration of the parasite during infection (2,12,13).…”
mentioning
confidence: 99%
“…72 14-3-3 proteins have been detected in the asexual form of the parasite, namely the tachyzoite stage, that is virulent in humans. 73 Moreover, it was demonstrated that, in this stage, 14-3-3 proteins from T. gondii induce hypermotility in infected host cells. 74 Alveolar echinococcosis (AE) is a rare parasitic disorder that occurs after ingestion of eggs of Echinococcus multilocularis.…”
Section: Intentionally Targetingmentioning
confidence: 98%
“…For example, the single 14-3-3 protein in Giardia duodenalis has been found to be modified post-translationally in vivo and involved in a number of cellular processes [10]. The genome of Toxoplasma gondii , another Apicomplexa n parasite, encodes four putative 14-3-3 proteins, at least one of which may be membrane associated and an excreted/secreted antigen, suggesting its possible role as a vaccine candidate [11].…”
Section: Introductionmentioning
confidence: 99%